ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN ARSIP BERBASIS WEB PADA SEKOLAH TINGGI ILMU TARBIYAH ( STIT ) KABUPATEN TEBO - Sukron Amin; Kondar Siahaan (LPPM Universitas Dinamika Bangsa, 2016)
In the processing of archiving documents study program at the Sekolah Tinggi Ilmu Tarbiyah (STIT) Tebo,special in compile each one document to the bookself, still using manually sistem and for lecturers whoborrowed the documents study programs have to come down and look for the documents to Kaprodi, and itsmake a system running slow , so the search for documents may be less than the maximum. That why to solved itswe need a system that can archive. The document to be more courses either in the form of web. The informationsystem will be designed with the Prototype method and system modeling using object-oriented modeling that usecase diagrams, activity diagrams, and class diagrams. The results of this research is to design a prototypesystem of Web-Based Records Management information At Sekolah Tinggi Ilmu Tarbiyah (STIT) Tebo. With thisinformation system can minimize the problem and is expected to make it better and faster in the archiving ofdocuments.